The social impact of globalization in the developing countries - Eddy Lee; Marco Vivarelli (Institute for the Study of Labor (IZA), 2006)
In this paper an ex-post measurable definition of globalization has been used, namely increasing trade openness and FDI. A general result is that the optimistic Heckscher-Ohlin/Stolper-Samuelson predictions do not apply, that is neither employment creation nor the decrease in within-country inequality are automatically assured by increasing trade and FDI. The other main findings of the paper are that: 1) the employment effect can be very diverse in different areas of the world, giving raise to concentration and marginalisation phenomena; 2) increasing trade and FDI do not emerge as the main culprits of increasing within-country income inequality in DCs, although some evidence emerges that import of capital goods may imply an increase in inequality via skill-biased technological change; 3)increasing trade seems to foster economic growth and absolute poverty alleviation, although some important counter-examples emerge.
Keywords: F02; O1; 330; trade; FDI; employment; poverty; within-country income inequality; Globalisierung; Direktinvestition; Beschäftigungseffekt; Armut; Einkommensverteilung; Entwicklungsländer